Pengetahuan dan sikap dokter gigi umum di kota semarang terhadap desain gtsl akrilik - Wirahadikusumah, Andy; Cetta Prayitno Putri, Nabila (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Removable partial dentures (RPD) is a dentures that replaces one or more missing teeth and open-pairs by patients. Acrylic resin is one of the basic materials for making RPD. When making a RPD, there are several things that dentists must pay attention to because dentists have a big responsibility in designing RPD. Objectives: To obtain an overview of the knowledge and attitudes of general dentist regarding designing removable partial denture acrylic. Material and Methods: This type of research is descriptive observational with a cross-sectional design. This research was conducted with 107 dentists as respondents. Data collection was obtained using a questionnaire that had been tested for validity and reliability, distributed via Google Forms to measure the knowledge and attitudes of dentists. Results: It was found that the majority of respondents aged 26 – 35 years were 61 people (57%), 81 people were female (75,7%), and 38 (35,5%) had practice experience for 5 – 10 years. Respondents in the good knowledge category were 80 people (74,8%), 26 people had adequate knowledge (24,3%), and 1 person had poor knowledge (0,9%). There were 89 respondents in the good attitude category (83,2%), 16 people adequate attitude (14,9%), and 2 people less attitude (1,9%). Conclusion: It was concluded that the knowledge and attitudes of general dentists regarding design of acrylic removable partial dentures were in the good category.